Capitalizing CIALCA’s 15 years of multi-actor, multi-stakeholder, actionable and adaptive research support for inclusive and sustainable knowledge ecosystems in the Great Lakes Region - Sartas, Murat; Remans, Roseline; Gotor, Elisabetta (2021)
Born out of integrating multiple interventions working in the Great Lakes Region, the Consortium for Improving Agriculture-based Livelihoods in Central Africa (CIALCA) has been conducting applied research and supporting collaborative efforts of international and national organisations working in the agricultural sector. It has been generating information and scientific and practical knowledge about different parts of the agricultural sectors in Burundi, Eastern Democratic Republic of Congo (DRC) and Rwanda and to a lesser extent in Uganda and Tanzania. In addition, due to its continuity and intensive capacity development efforts, the knowledge and the science generated by CIALCA has been spreading for more than a decade and is currently being utilised by many researchers working in the Great Lakes Region.